2014
DOI: 10.1007/s00417-014-2862-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and biometry of horizontal extraocular muscle tendons using optical coherence tomography

Abstract: It is possible to visualize and measure HRMTs using AS-OCT. Measurements of the HRM, as well as the surrounding external ocular tissues, can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…OCT has a potential use in the diagnosis and monitoring of the therapeutic response in extraocular muscle diseases. 9,10 This study found that SS-OCT and SD-OCT are reliable and reproducible techniques for measuring the limbus insertion distance and the thickness of the horizontal rectus muscles, with good agreement between the different devices.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…OCT has a potential use in the diagnosis and monitoring of the therapeutic response in extraocular muscle diseases. 9,10 This study found that SS-OCT and SD-OCT are reliable and reproducible techniques for measuring the limbus insertion distance and the thickness of the horizontal rectus muscles, with good agreement between the different devices.…”
Section: Discussionmentioning
confidence: 61%
“…Park et al 16 also reported excellent reproducibility in measuring the horizontal extraocular muscle insertion distance with TD-OCT (ICC ≥ 0.96). Salcedo-Villanueva et al 9 reported excellent intra-observer reproducibility (ICC = 0.981) and inter-observer agreement (ICC = 0.834) when measuring the muscle thickness. In the current study, the reproducibility values and the percentage of identification were slightly higher with the SS-OCT device than with the SD-OCT devices.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…20 Salcedo-Villanueva et al imaged the horizontal extraocular muscles and measured the lengths of tendons and thickness of the muscles, conjunctival epithelium, sclera, and Tenon's capsule. 21 These studies did not measure the superior and inferior rectus muscle insertions and the measurements of the insertions were taken from an arbitrary calculated limbus, from either the anterior chamber angle or scleral spur. The study by Ngo et al is the only one to date that has imaged the extraocular rectus muscles with AS-OCT in a pediatric population, re-operated muscles, and imaged the vertical rectus muscles.…”
Section: Introductionmentioning
confidence: 99%